Improving Critical Thinking Skills in Mathematics of Class IV Students CTL Model Based on Essay Tests - Oliviasari, Elvira; R, Rizky Tsalasa A.; Na’miyah, Husniatun; Lauren, Hana (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2024)
Contextual learning begins by providing knowledge, experiences, and real-life contexts related to the subjects taught in school. Students are expected to apply this knowledge and experience in their daily lives, not just to grasp these values superficially. Students need to internalize and practice these values in their everyday lives. The basic contextual learning theory is Constructivism, which emphasizes active understanding in learning mathematics to construct new knowledge from past experiences and expertise. Based on research data, it's evident that the contextual teaching and learning (CTL) model has positively impacted students' critical thinking skills. This is reflected in the achievement of success indicators set and declared as achieved in cycle II of the learning process.